Peripheral neuropathy symptoms in wild type transthyretin amyloidosis. Issue 3 (27th July 2020) - Wajnsztajn Yungher, Fernanda; Kim, Arreum; Boehme, Amelia; Kleyman, Inna; Weimer, Louis H; Maurer, Mathew S; Brannagan, Thomas H
Abstract: To propose a correlation between polyneuropathy and ATTRwt based on retrospective analysis of patients with ATTRwt. We reviewed 151 ATTRwt patients followed by the amyloid cardiac clinic (group A) for symptoms of neuropathy and 12 patients with ATTRwt evaluated in the Neurology Department (group B) with objective measures of neuropathy. Medical history, electrodiagnosis, laboratory and skin biopsies were assessed; 30.5% of group A had neuropathy symptoms. Alternative explanations for neuropathy symptoms were explored, including, age, gender, BMI, diabetes mellitus, B12 deficiency. No difference was observed for BMI, age, gender and spine disease for those with and without neuropathic symptoms ( P > .05). All of group B (n = 12) were diagnosed with neuropathy, confirmed by electrodiagnostic testing or skin biopsy, while two patients had not yet developed cardiac symptoms. We observe a higher prevalence of neuropathic symptoms in ATTRwt patients than previously believed. Neuropathic symptoms may precede cardiac symptoms. Our findings suggest a possible causative relationship that requires further investigation.